Democratic resilience in the twenty-first century: search for an analytical framework and explorative analysis - Croissant, Aurel; Lott, Lars (Political studies, 2025)
Why are some democracies more resilient than others? How can their resilience be improved? Answering these questions requires valid conceptualization and reliable measures of democratic resilience. This study presents a novel conceptualization and measurements of democratic resilience. It differentiates between democratic resilience as regime performance and regime capacity and introduces the Democratic Resilience Capacity Index. The index is the first and only measure available to empirically compare the ability of democracies to become or to remain resilient. We demonstrate the usefulness of our approach for empirical research through an exploratory study of 103 democracies since 2000. We find that resilience capacity strengthens the ability of a democracy to prevent a substantial loss of its democratic qualities and regime breakdown, but not its ability to recover from autocratization. This suggests that different forms of democratic resilience, though temporally connected, depend on different forms or combinations of resilience capacities.